UNIVERSITY EDUCATION INNOVATION ON POLICIES FOR TEACHERS IN VIETNAM - Nhan, Duong (IJRDO- Journal of Educational Research, 2018)
Education reform is a controversial topic. In the situation of industrialization and modernization and international integration, the human resources has become so important that it determines the success of the national development. The Party and Government have paid great attention to education and training. In spite of the great achievements we have made, there are a lot of issues that need to be addressed. By analyzing the current policies for teachers, this paper proposes some solutions for resolving those issues and creating significant changes in the future.